GAMBARAN STATUS GIZI PADA BALITA DI POLI KIA DI UPT PUSKESMAS GAJAH MADA TAHUN 2018 - Fatma Rokiyah; Madinah (Jurnal Kesehatan Husada Gemilang, 2020)
The nutritional status of toddler is an important factor because their development period is vulnerable to nutrition. More than a third of child deaths in the world are related to the problem of malnutrition every years. Gajah Mada Tembilahan Health Center recorded in 2017 the number of malnutrition toddlers is 45 and increased in 2018 as many as 49 toddlers. The study aim to determine the overview of toddlers nutritional status at MCH Poly, PHC Gajah Mada Tembilahan in 2018. The research is descriptive with a cross sectional design and a retrospective approach. The study was conducted at the MCH Poly, PHC Gajah Mada Tembilahan on August 8th to 17th 2019. The population is used total sampling was all toddlers aged 12-59 months who had visited the MCH Poly of PHC Gajah Mada Tembilahan in 2018 with number 634 toddlers. The results obtained, from 634 toddlers, 386 (60.9%) toddlers with good nutritional status. It is hoped that the research institution can continue to provide counseling and education for mothers toddlers to continuous monitoring the growth and development of their toddlers to reduce the number of malnutrition in future.